Enhancing Corporate Integrity: Profitability, Transfer Pricing, and Tax Avoidance with the Role of Bonus Mechanisms and Stewardship Theory - Wulandari, Dian Sulistyorini; Yulianti, Vista; Fuadi, Agus (Pusat P2M Politeknik Negeri Batam, 2025)
This study examines the effect of transfer pricing and bonus mechanisms on tax avoidance. It tests profitability as a moderating variable in multinational companies. Grounded in Stewardship Theory, the research explores whether managerial incentives and corporate profitability influence firms’ tax behavior. It emphasizes the balance between financial performance and ethical tax practices. A quantitative approach was used with secondary data from the financial reports of industrial sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2022. The sample was selected through purposive sampling, consisting of 21 companies. Panel data regression analysis was conducted using the Ordinary Least Squares (OLS) method, supported by Chow, Hausman, and Lagrange Multiplier (LM) tests to determine the most appropriate model. The results show that both transfer pricing and bonus mechanisms have a significant positive effect on tax avoidance. This indicates that multinational firms use intra-group transactions and performance-based incentives to minimize tax burdens. However, profitability does not significantly moderate these relationships. This suggests that firm performance alone does not weaken or strengthen the impact of transfer pricing and bonus mechanisms on tax avoidance. These findings contribute to the literature on corporate governance and tax planning by providing empirical evidence on the interplay between managerial incentives, profitability, and ethical financial behavior. The research offers valuable implications for policymakers and companies in developing responsible compensation systems and regulatory frameworks to curb aggressive tax practices.